The Effect of Good Corporate Governance and Accounting Information Systems on the Quality of Financial Statements - Zahra Harlianti Sujana (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2021)
This study aims to determine how the influence of good corporate governance and accounting information systems on the quality of financial reports at PT Pos Indonesia (Persero) Bandung City. The factors tested in this study are good corporate governance and accounting information systems as independent variables. Meanwhile, the quality of financial reports is the dependent variable. The research method used in this research is the verification method. The population in this study were employees of the finance department at PT.Pos Indonesia (Persero) Bandung. The sampling technique used in this study is a non-probability sampling technique with a saturated sampling method, so that the sample in this study was 34 employees. The analytical method used in this study is multiple linear regression analysis using the Statistical Package for Social Sciences (SPSS) Ver.23.00. The results of research partially and simultaneously show that good corporate governance and accounting information systems affect the quality of financial reports at PT Pos Indonesia (Persero) Bandung City. In addition, the magnitude of the influence of good corporate governance and accounting information systems in contributing to the influence of the quality of financial reports is 55.3%. Keywords: Good Corporate Governance, Accounting Information Systems, and Quality of Financial Statements.